Method for preparing net-shaped heterostructure nickel-based coating through laser cladding

The nickel-based coating with a mesh heterostructure was prepared on the Q235 steel substrate through laser cladding technology. Mo2C and Ni2Si were used as reinforced phases to solve the problem that metal materials could not take into account both strength and ductility, and achieve high strength Combination with good ductility.

CN119465136APending Publication Date: 2025-02-18YANSHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411652784.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The difficulty in taking into account the strength and ductility of existing metal materials, resulting in insufficient performance in many applications.

Method used

The nickel-based coating with a mesh heterostructure was prepared on the surface of the Q235 steel substrate by laser cladding technology. Mo2C and Ni2Si were used as reinforced phases to present a three-dimensional network distribution along the grain boundary to improve the strength and ductility of the coating.

Benefits of technology

It has achieved the significant improvement of the ductility of the nickel-based coating while ensuring high strength, and solved the shortcomings of traditional metal materials in the strength-ductility trade-off.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465136A_ABST
    Figure CN119465136A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a net-shaped heterostructure nickel-based coating through laser cladding, and belongs to the technical field of laser cladding, and the method comprises the following steps: pre-arranging nickel-based alloy powder on the surface of a Q235 steel substrate by using absolute ethyl alcohol and a mold, and after drying, carrying out single-pass cladding by using a laser cladding technology to obtain the net-shaped heterostructure nickel-based coating. A nickel-based coating with a net-shaped heterostructure is manufactured on the surface of the Q235 steel substrate; wherein Mo2C and Ni2Si are generated through a laser in-situ reaction, a reinforcing phase is distributed in a three-dimensional network shape along a crystal boundary to form a network heterostructure, the effect of refining crystal grains is achieved by adding the reinforcing phase, and the strength of the coating is effectively improved; the net-shaped heterostructure has heterogeneous deformation induction (HDI) strengthening and hardening effects, and the strength and ductility of the coating material can be effectively improved through combination of multiple strengthening mechanisms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser cladding, and in particular relates to a method for preparing a nickel-based coating with a reticular heterogeneous structure by laser cladding. Background Art

[0002] The strength-ductility trade-off of engineering metal materials has always been a difficult problem that has troubled scientists. Generally speaking, metal materials with high strength have poor ductility, and vice versa. The poor ductility of high-strength metals limits their application in many advanced technologies. In recent years, heterostructured (HS) materials have become a hot topic of research due to their unique strengthening mechanism and the characteristics of balancing strength and ductility. It is considered to be one of the effective ways to solve the strength-plasticity mismatch. Heterostructured materials include multilayer structures, gradient structures, harmonic structures, and dual-phase structures. What they have in common is that they are composed of heterogeneous regions with large differences in performance. During the deformation process, they will produce significant heterogeneous deformation induced (HDI) strengthening and hardening effects, and have an excellent combination of strength and ductility / toughness.

[0003] In 1969, Hansen proposed to strengthen aluminum alloys through a three-dimensional network formed by alumina particles. The study found that the hard particle network can effectively strengthen aluminum and can play an almost the same effect as the uniform dispersion of particles. Metal matrix composites with a mesh structure can also be considered as a heterogeneous structure. At present, the most studied mesh structure reinforced metal matrix composite is TiB reinforced titanium matrix composite. Huang et al. proposed and prepared a three-dimensional quasi-continuous network (3DQCN) microstructure in TiB-Ti composites. The method used was hot pressing and sintering. The in-situ synthesized TiB whisker reinforcement phase was distributed around the matrix particles to form a three-dimensional continuous network, which wrapped a soft matrix phase. This mesh heterogeneous structure can play a better reinforcement effect. Hu et al. used laser deposition-additive manufacturing (LD-AM) technology to generate a three-dimensional quasi-continuous mesh structure in situ in Ti-based composites. The results showed that the 3DQCN structure effectively improved the toughness of TiB-Ti composites. Therefore, this structure can be introduced into metal-based coatings as a method to improve the strength and toughness of materials.

[0004] Compared with other technologies, the laser preparation method has the characteristics of high supercooling and high energy density. By utilizing the exclusive effect of the grain growth interface during the liquid phase solidification process in the molten pool, the distribution of the reinforcement phase along the grain boundary can be regulated to form a network; the advantage of the in-situ self-generation method over the direct addition method is that the reinforcement phase has good compatibility with the metal matrix, no surface pollution, less energy required, and can play a better role in strengthening the coating. Nickel-based materials are common additive manufacturing materials, and there are few studies on the network reinforcement structure in nickel-based materials, and they rarely involve the laser field. Therefore, the present invention selects nickel as the matrix material and generates a coating with a network heterogeneous structure in situ through laser technology to provide a more effective strengthening strategy. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a nickel-based coating with a network heterogeneous structure by laser cladding, and a single-pass cladding is performed on the surface of a Q235 steel substrate using laser cladding technology to obtain a nickel-based coating with a network heterogeneous structure. The base material of the coating is metal Ni, and Mo2C and Ni2Si are generated by laser in-situ reaction. The reinforcing phase is distributed in a three-dimensional network along the grain boundary, which improves the strength of the coating while maintaining good ductility.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a nickel-based coating with a network heterogeneous structure by laser cladding comprises the following steps: Step A, preparing alloy powder, the specific composition includes 0.5-1.15%wt.%C, 14-30wt.%MoSi2, and the balance is Ni, wherein the atomic ratio of Mo to C is 2:1; Step B, adding anhydrous ethanol to the alloy powder and stirring it into a muddy state, coating it evenly on the surface of the steel substrate, and drying it; Step C: preheating the substrate in a heat preservation furnace, and cladding the alloy powder on the steel substrate using laser cladding technology to obtain a nickel-based composite coating with a three-dimensional network heterogeneous structure.

[0007] A further improvement of the technical solution of the present invention is that the reinforcement phase of the nickel-based composite coating is distributed in a three-dimensional network along the grain boundaries, and the reinforcement phase contains substances Mo2C and Ni2Si.

[0008] A further improvement of the technical solution of the present invention is that in step A, the Ni source is metal Ni powder and Ni-graphite powder, the average particle size of the metal Ni powder is 45~100μm, and the purity is 99.5%; the average particle size of the MoSi2 powder is 3~5μm, and the purity is 99.9%; C comes from Ni-graphite powder, wherein the C content is 25wt.%, the average particle size is 45~100μm, and the purity is 99.5%.

[0009] A further improvement of the technical solution of the present invention is that the alloy powder is prepared by mixing powder in a "V" type powder mixer, the speed of the powder mixer is 20r / min, and the mixing time is 12h.

[0010] A further improvement of the technical solution of the present invention is that: the steel substrate includes a Q235 steel substrate, and before laser cladding, an angle grinder is used to grind the substrate surface to remove oxides and impurities, and anhydrous ethanol is used to clean the surface, and the substrate is naturally air-dried.

[0011] A further improvement of the technical solution of the present invention is that in step B, a frame-shaped mold can be used to pre-dispose the muddy alloy powder evenly on the steel substrate, the preset thickness of the alloy powder is 1 mm, and it is dried at 100° C. for 20 minutes.

[0012] The further improvement of the technical solution of the present invention is that: in step C, the sample with the pre-set alloy powder is placed in a heat preservation device for preheating, the preheating temperature is 700° C., the preheating time is 5 minutes, and argon gas is continuously introduced for protection during the preheating process.

[0013] The further improvement of the technical solution of the present invention is that the laser power P of the laser cladding alloy powder in step C is 2400W, the scanning speed V is 3mm / s, the spot size D is 10mm×1mm, and argon gas protection is continuously introduced during the laser cladding process, and the argon gas flow rate is 8L / min.

[0014] The present invention utilizes the in-situ reaction of MoSi2 and C to introduce a high-temperature precipitate phase Mo2C, which is first precipitated in the early stage of the solidification process. Subsequently, the interface repulsive effect on the precipitate phase during the growth of matrix Ni grains is utilized to push Mo2C to the boundary so that it is distributed along the grain boundary to form a three-dimensional network-like heterogeneous structure.

[0015] After the laser cladding is completed, the sample is taken out and cooled at room temperature. Then, the coating surface is polished with an angle grinder to remove oxides and impurities, and the forming quality of the coating is checked. The coating preparation is completed.

[0016] Due to the adoption of the above technical solution, the beneficial effects achieved by the present invention are as follows: The method of the present application effectively improves the common "strength-ductility trade-off" problem of metals, introduces high-strength Mo2C as a reinforcing phase, and realizes a three-dimensional network distribution of the reinforcing phase to form a nickel-based coating with a network heterogeneous structure. The HDI strengthening and hardening effects improve the ductility of the coating while ensuring its strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The process of preparing samples and the schematic diagram of the coating structure of Examples 1-5 of the present invention; Figure 2The calculation results of Gibbs free energy of the molten pool reaction in the process of Examples 1-5 of the present invention; Figure 3 The surface morphology of the coating obtained in Examples 1-5 of the present invention; Figure 4 This is a SEM image of the coating obtained in Example 1 of the present invention; Figure 5 This is a SEM image of the coating obtained in Example 2 of the present invention; Figure 6 This is a three-dimensional microstructure diagram of the coating obtained in Example 1 of the present invention; Figure 7 This is the EDS analysis of the coating obtained in Example 1 of the present invention; Figure 8 This is the EDS analysis of the coating obtained in Example 2 of the present invention; Fig. 9 XRD analysis of the coatings obtained in Examples 1-5 of the present invention; Fig.10 Schematic diagram of the tensile specimen size and processing method of the coating obtained in Examples 1-5 of the present invention; Fig.11 1 is the tensile stress-strain curve of the coating obtained in Examples 1-5 of the present invention. DETAILED DESCRIPTION

[0018] The method provided by the present invention will be described in detail below through the accompanying drawings and specific examples. The examples only relate to the preferred implementation schemes of the present invention and they cannot be understood as limiting the scope of protection of the present invention.

[0019] Example 1 like Figure 1 As shown in the figure, the sample preparation process and the schematic diagram of the coating structure are shown. The selected substrate is Q235 steel plate with a size of 40mm×15mm×5mm (length×width×height). Before the experiment, an electric angle grinder was used to grind the surface of the steel plate to remove oxides, oil stains and other impurities. The surface of the steel plate was wiped clean with anhydrous ethanol and allowed to air dry naturally at room temperature.

[0020] Attached Figure 2 is the Gibbs free energy of the chemical reactions that may occur in the molten pool ( ΔG ) calculation results show that the Gibbs free energy of reaction (4) to generate Mo2C is negative within the experimental temperature range, indicating that the reaction can proceed spontaneously. Although Mo and C may also generate products such as MoC and Mo3C2, the reaction products can be controlled by adjusting the content ratio of Mo to C. Therefore, the atomic ratio of Mo to C in the alloy powder is selected to be 2:1, and then the mass ratio of MoSi2 powder to nickel-coated graphite (Ni-graphite) powder is determined.

[0021] Weigh and mix the powders according to the preset weight percentage of 82wt.%Ni+0.68wt.%C+17.32wt.%MoSi2, where the average particle size of the metal Ni powder is 45~100μm and the purity is 99.5%; the average particle size of the MoSi2 powder is 3~5μm and the purity is 99.9%; the C content of the Ni-graphite powder is 25wt.%, the average particle size is 45~100μm, and the purity is 99.5%. Put the mixed powder into a "V" type powder mixer for mixing at a speed of 20r / min for 12h to obtain the cladding alloy powder.

[0022] The mold size is 30mm×10mm×1mm (length×width×height). Take a certain amount of alloy powder and place it in a beaker. Add an appropriate amount of anhydrous ethanol and stir it into a muddy state. Place the mold on the surface of the Q235 steel substrate and evenly coat the muddy powder in the hollow area. Remove the mold after it is slightly dry, so that the powder is evenly and flatly fixed on the surface of the steel substrate with a thickness of 1mm. Put the sample into a drying oven and keep it at 100℃ for 20 minutes to completely evaporate the water and ethanol in the powder.

[0023] Before preheating the substrate, the temperature inside the heat preservation device was raised to 700°C, and then the dried sample was placed in the device, and the temperature was maintained at 700°C for 5 minutes. During the preheating process, argon gas protection was continuously introduced to prevent oxidation, and the argon gas flow rate was 8L / min.

[0024] Laser cladding experiment: The laser emitter on the robot arm is controlled to move to the top of the sample, the laser spot is located in front of the preset powder, the laser beam wavelength is 1.064μm, the laser power is 2400W, the scanning speed is 3mm / s, the spot size is 10mm×1mm, the preset powder layer thickness is 1mm, and the laser processing process is carried out under argon protection, and the argon flow rate is 8L / min. After the laser cladding is completed, the sample is taken out and cooled at room temperature, and then the coating surface is polished with an angle grinder to remove oxides and impurities, cleaned with anhydrous ethanol and air-dried, and the forming quality of the coating is checked. The heterostructure nickel-based coating is prepared.

[0025] The high-temperature precipitate phase is introduced into the matrix by in-situ reaction, so that it can solidify before the matrix. Then, the repulsion of the precipitate phase by the matrix grain growth process is utilized to make it distribute along the grain boundary to form a three-dimensional network heterogeneous structure.

[0026] Attached Figure 3 The macroscopic morphology of the prepared coating is shown in Figure 2. The coating surface is smooth and has no defects such as cracks and pores, indicating that the coating has good forming quality under this process parameter. Figure 4 The SEM image of the coating is attached. Figure 6 The three-dimensional microstructure diagram shows that the reinforcement phase presents a three-dimensional network distribution at the grain boundary. Figure 7 EDS analysis and attachment Fig. 9 The XRD analysis results show that the network reinforcement phases in the coating are Mo2C and Ni2Si.

[0027] The prepared samples were Fig.10 The size and method shown in the figure are used to process the tensile specimens using a wire cutting machine, and the cut surface is polished and leveled for tensile performance testing. The results are shown in the attached figure. Fig.11 As shown, the ultimate tensile strength (UTS) of the coating is 756 MPa and the elongation (EI) is 21.1%, with a good combination of strength and plasticity.

[0028] Example 2 The difference between this embodiment and embodiment 1 is that the alloy powder ratio used is 85wt.%Ni+0.56wt.%C+14.44wt.%MoSi2, and the rest is the same as embodiment 1, and a net-like heterogeneous structure nickel-based coating can be obtained. Figure 5 The SEM image of the coating is attached. Figure 8 is the EDS analysis result of the coating, which shows that the reinforcement phase is distributed in a network at the grain boundary of the matrix, but compared with Example 1, the reinforcement phase is reduced and the grain size is larger; Fig.11 The tensile test results show that the coating has an ultimate tensile strength of 715MPa and an elongation of 29.7%.

[0029] Example 3 The difference between this embodiment and embodiment 1 is that the alloy powder ratio used is 79wt.%Ni+0.75wt.%C+19.35wt.%MoSi2, and the rest is the same as embodiment 1, and a network heterogeneous structure nickel-based coating can be obtained.

[0030] Example 4 The difference between this embodiment and embodiment 1 is that the alloy powder ratio used is 75wt.%Ni+0.94wt.%C+24.06wt.%MoSi2, and the rest is the same as embodiment 1, and a network heterogeneous structure nickel-based coating can be obtained.

[0031] Example 5 The difference between this embodiment and embodiment 1 is that the alloy powder ratio used is 70wt.%Ni+1.12wt.%C+28.88wt.%MoSi2, and the rest is the same as embodiment 1, and a network heterostructure nickel-based coating can be obtained.

[0032] Matters not covered by the present invention are known technologies.

[0033] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a network heterogeneous structure nickel-based coating by laser cladding, characterized in that: Step A, preparing alloy powder, the specific composition includes 0.5-1.15%wt.%C, 14-30wt.%MoSi2, and the balance is Ni, wherein the atomic ratio of Mo to C is 2:1; Step B, adding anhydrous ethanol to the alloy powder and stirring it into a muddy state, coating it evenly on the surface of the steel substrate, and drying it; Step C: preheating the substrate in a heat preservation furnace, and cladding the alloy powder on the steel substrate using laser cladding technology to obtain a nickel-based composite coating with a three-dimensional network heterogeneous structure.

2. The method for preparing a network heterogeneous structure nickel-based coating by laser cladding according to claim 1, characterized in that: The reinforcement phase of the nickel-based composite coating is distributed in a three-dimensional network along the grain boundary, and the reinforcement phase contains Mo2C and Ni2Si.

3. The method for preparing a network heterogeneous structure nickel-based coating by laser cladding according to claim 1, characterized in that: In step A, Ni is sourced from metal Ni powder and Ni-graphite powder, the average particle size of metal Ni powder is 45-100 μm, and the purity is 99.5%; the average particle size of MoSi2 powder is 3-5 μm, and the purity is 99.9%; C is derived from Ni-graphite powder, wherein the C content is 25 wt.%, the average particle size is 45-100 μm, and the purity is 99.5%.

4. The method for preparing a network heterogeneous structure nickel-based coating by laser cladding according to claim 1, characterized in that: The alloy powder is prepared by mixing powder in a "V" type powder mixer, the speed of the powder mixer is 20r / min, and the mixing time is 12h.

5. The method for preparing a network heterogeneous structure nickel-based coating by laser cladding according to claim 1, characterized in that: The steel substrate includes a Q235 steel substrate. Before laser cladding, an angle grinder is used to grind the surface of the substrate to remove oxides and impurities, and anhydrous ethanol is used to clean the surface, and the substrate is naturally air-dried.

6. The method for preparing a network heterogeneous structure nickel-based coating by laser cladding according to claim 1, characterized in that: In step B, a frame-shaped mold is used to pre-place muddy alloy powder on a steel substrate. The pre-placed thickness of the alloy powder is 1 mm, and the powder is dried at 100° C. for 20 minutes.

7. The method for preparing a network heterogeneous structure nickel-based coating by laser cladding according to claim 1, characterized in that: Step C: Place the sample with the alloy powder pre-set in a heat preservation device for preheating at a temperature of 700° C. for 5 minutes, and continuously introduce argon gas for protection during the preheating process.

8. The method for preparing a network heterogeneous structure nickel-based coating by laser cladding according to claim 1, characterized in that: In step C, the laser power P of the laser cladding alloy powder is 2400 W, the scanning speed V is 3 mm / s, the spot size D is 10 mm×1 mm, and argon gas protection is continuously introduced during the laser cladding process, and the argon gas flow rate is 8 L / min.